2018
DOI: 10.1002/ams2.328
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative fluid restriction for trauma patients with hemorrhagic shock decreases ventilator days

Abstract: AimIn recent years, with the concept of damage control resuscitation, hemostasis and preoperative fluid restriction have been carried out, but there is controversy regarding the effectiveness of fluid restriction.MethodsFrom April 2007 to March 2013, 101 trauma patients presented with hemorrhagic shock (systolic blood pressure ≤90 mmHg) at the prehospital or emergency department and were admitted to Hyogo Emergency Medical Center (Hyogo, Japan). They underwent emergency hemostasis by surgery and transcatheter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“… 24 Previous studies have found that those treated with preoperative SFM, and not RFM, required higher volumes of intraoperative fluid. 2 , 4 The differing results could be because of the underlying diagnoses and characteristics of trauma patients included. Matsuyama et al 4 observed that hemodynamically unstable trauma patients treated with SFM received significantly more fluids intraoperatively, but no difference in postoperative fluid volumes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 24 Previous studies have found that those treated with preoperative SFM, and not RFM, required higher volumes of intraoperative fluid. 2 , 4 The differing results could be because of the underlying diagnoses and characteristics of trauma patients included. Matsuyama et al 4 observed that hemodynamically unstable trauma patients treated with SFM received significantly more fluids intraoperatively, but no difference in postoperative fluid volumes.…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous publications reported that this standard fluid management (SFM) led to an increase in ventilator days, mortality, pulmonary edema, cerebral edema, intracranial pressure, acute respiratory distress syndrome (ARDS), development of hyperchloremic metabolic acidosis, acute kidney injury (AKI) for susceptible patients, increased hemorrhage volume, and increased time to hemostasis. 2–11 Increased time to bleeding control and increased bleeding volume for those with SFM may be attributable to hemodilution of coagulation factors, decreasing blood viscosity, detachment of the initial clot, and thrombus shift. 2–10…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations